Relevansi Hukum Perdata Islam dalam Merespons Perubahan Sosial di Indonesia: Analisis Yuridis dan Filosofis - Muhammad Yayad Ari Hidayat; Muhammad Taufiqurrahman; Pebriyan Nugroho; Asrizal Saiin (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
Islamic Civil Law plays a significant role in regulating social, economic, and religious relations in Indonesia. In the context of rapid social transformation, the application of Islamic civil law within Indonesia’s pluralistic society requires critical examination from both juridical and philosophical perspectives. One of the main challenges lies in ensuring that Islamic civil law remains responsive to dynamic social change while preserving its foundational religious and moral principles. Accordingly, this study aims to analyze the relevance of Islamic civil law in addressing social change in Indonesia and to examine its application through juridical and philosophical approaches. This research employs a qualitative library-based method with normative analysis, drawing on legal literature, scholarly books, academic journals, and other relevant sources related to Islamic civil law and social change in Indonesia. The findings indicate that Islamic civil law remains highly relevant in responding to social change, particularly in the regulation of family relations, economic activities, and social interactions. From a juridical perspective, Islamic civil law demonstrates adaptability in accommodating evolving societal conditions. Philosophically, it maintains a balance between adherence to religious values and responsiveness to contemporary social needs. This combination of juridical flexibility and philosophical consistency is essential to sustaining the effectiveness and relevance of Islamic civil law within Indonesia’s continually evolving social context.